TIAs pathway genes and associated miRNA identification in Vinca minor: supporting aspidosperma and eburnamine alkaloids linkage via transcriptomic analysis - Verma, Priyanka; Singh, Noopur; Khan, Shamshad Ahmad; Mathur, Ajay Kumar; Sharma, Ashok; Jamal, Farrukh (Physiology and Molecular Biology of Plants, 2020)
V. minorcontains monomeric eburnamine-type of indole alkaloids having utilization as a neuro-medicinal plant. The biosynthetic pathway studies using miRNAs has been the focal point for plant genomic research in recent years and this technique is utilized to get an insight into a possible pathway level study inV. minoras understanding of genes in this prized medicinal plant is meagrely understood. The de novo transcriptomic analysis using Illumina Next gen sequencing has been performed in glasshouse shifted plant and transformed roots to elucidate the possible non confirmed steps of terpenoid indole alkaloids (TIAs) pathway inV. minor. A putative TIA pathway is elucidated in the study including twelve possible TIAs biosynthetic genes. The specific miRNA associated with TIAs pathway were identified and their roles were discussed for the first time inV. minor. The comparative analysis of transcriptomic data of glasshouse shifted plant and transformed roots showed that the raw reads of transformed roots were higher (83,740,316) compared to glasshouse shifted plant (67,733,538). The EST-SSR prediction showed the maximum common repeats among glasshouse shifted plant and transformed roots, although small variation was found in trinucleotide repeats restricted to glasshouse shifted plant. The study reveals overall 37 miRNAs which were observed to be true and can have a role in pathway as they can regulate the growth and alkaloid production. The identification of putative pathway genes plays an important role in establishing linkage between Aspidosperma and Eburnamine alkaloids.
Keywords: de novo transcriptomic analysis; EST-SSR; miRNA; Terpenoid indole alkaloids; Vinca minor